A Fuzzy Semibipolar Soft Filter and its Association with Green's Relation $\mathcal{N}$ (European Journal of Pure and Applied Mathematics, 2024)
This paper introduces the concept of fuzzy semibipolar soft filters in ordered groupoids. It is defined in the form of fuzzy semibipolar soft sets over universal sets. Then, a corresponding example is proposed. A necessary and sufficient condition for fuzzy semibipolar soft filters is provided. Finally, Green's relation $\mathcal{N}$ on ordered groupoids is described in terms of fuzzy semibipolar soft filters.
Keywords: Green's relation; Ordered groupoid; Fuzzy filter; Soft set